Apakah Berpengaruh Perawatan Luka Modern terhadap Tingkat Penyembuhan Luka pada Ulkus Diabetik? - Padila Padila; Juli Andri (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of modern wound care on the wound healing rate of diabetic ulcers at Dr. Sobirin Musirawas Regional General Hospital. This study was quantitative with an analytical approach. The research design used a pre-experimental approach with a one-group pre-test and post-test design. The results showed a more significant effect of modern wound care on the assessment of necrotic tissue count (P=0.003) and granulation tissue (P=0.003). Meanwhile, the average wound healing rate in diabetic ulcers before modern wound care was 35.20 and after modern wound care was 30.67. The results of the paired t-test showed a P=0.004. In conclusion, modern wound care has an effect on the wound healing rate of diabetic ulcers.   Keywords: Modern Wound Care, Wound Healing Rate, Diabetic Ulcers